(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This study examines global and local demographic trends with a focus on the Kyrgyz Republic. Against the backdrop of declining birth rates, population aging, and rapid urbanization worldwide, Kyrgyzstan demonstrates a unique trajectory—population growth driven by internal migration coupled with a sharp decline in urban birth rates. A comparative analysis of demographic data from 2019 to 2023 reveals significant regional imbalances and institutional gaps in the country’s population policy. Since 2005, the absence of a specialized governmental body for demographic forecasting has weakened the state’s capacity to address current and future demographic challenges. Drawing on international experience, the paper proposes strategic recommendations, including the development of a national demographic strategy, enhanced support for young families, and investment in regional infrastructure. The findings are relevant for policymakers, researchers, and experts working in the fields of sustainable development, migration, and social policy.